Study of Distribution, Potential and Habitat of Harpullia arborea in the Frame of Establishment of In-Situ Gene Bank at Kerinci Seblat National Park - Sambas Basuni; Haidir . (Media Konservasi, 1997)
The study was conducted at Muara Emat and Tamiai Resort of Karinci Seblat Nationel Park. The study was d o r i g 4 for d i r h m n e t of " in situ gene bank of H. arborea ". Transccts, which were combined with square plots, was usod fiir vogetahn anrlysis. Individual abundance, fkquency and dominance were measured in five transccts consist of 59 plots. The local distribution pattern of H. arbona aggrcgative; the number of individual of tm is smaller than pole, sapling and seedling. There was some poaching for H. arbona's trees andcaused the number of individual of tree level become small. 6 ind./ha; compared with pole which had 86 ind.iha, sapling 468 i n d h ot 3664 ind./ha for seedling. Them aro 70 species of another plants, some of theese plants has high degree of association with H. Arborea such as SmHria spp., Aglaia aqentea, Anisophyllea distichs, Shorea arabida, Macaranga Iypoleuca, Payem lanceolata . and Dfospyms nnaing@. Theimplication of this study is : because of i d distribution pattern of H. arborea was aggmgative. the area delliniation for in situ gsne bank purpow is easy to crury out. The area unit is small. but they am distributed in the entire area of national park.ffib h i : P h n a nutfah, bank plasma nutfah, in-dtu dm ex-dtu, dbpersi, kekrribuq habitat.